COSTS OF ACCIDENTS IN THE PERUVIAN MINING (1994-1998) - Acero R., Tomás (2006)
The issue is to determine the cost of accidents in mining country. after identifying the work performed by persons related to the accident and the actions that need to comply with company according to law, in order to determine the amount of losses that could cause accidents to companies